The Effect of The Use of Video on English Vocabulary Mastery of The Elementary Second Level Students at SDN 018 Samarinda - Widi Syahtia Pane; Godefridus Bali Geroda (Borneo Educational Journal (Borju), 2019)
Vocabulary is one of language components that plays an important role in communication. Through vocabulary, students can develop the four skills in English language such as listening, reading, writing, and speaking. There are many ways in teaching vocabulary and increasing vocabulary mastery. In this study, the writer used video as a technique.   In this study, the writer wants to found out that has any significant effect of the use of Video on English vocabulary mastery of the elementary second level students at SDN 018 Samarinda.The design of this study was pre-experimental design. The writer gave pre-test, treatment, and post-test to one group. The sample of this study was 30 students of the elementary second level students at SDN 018 Samarinda. In analyzing data, the writer used t-test to find out the significance difference between the result before treatment (pre-test) and after treatment (post-test).In pre-test, from 30 students, 7 students got A (excellent), 6 students got B (good), 7 students got C (fair), 6 students got D (poor), and 4 students got E (fail). In post-test, from 30 students, 13 students got A (excellent), 8 students got B (good), 8 students got C (fair), 1 student got D (poor), and no students got E (fail). The mean score of vocabulary before treatment (pre-test) was fair (67,7) and the mean score of vocabulary after treatment (post-test) was good (78,7). The result of the findings of the study showed t-count (6.358) is greater ( ˃ ) than t-table (2.045) at level of significant (p) = 5% and df = 29. It means the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that the use of Video give very significant effects on vocabulary to the elementary second level students of SDN 018 Samarinda